A computational examination of conjugate heat transfer during microchannel flow boiling using finite element analysis - Burk, Bryan E., author; Bandhauer, Todd M., advisor; Windom, Bret C., committee member; Henry, Charles S., committee member (Colorado State University. Libraries, 2018)
As technology advances, electronic components continue to produce more heat while at the same time growing smaller and being arranged in ever more compact packages. This has created the need for new thermal management systems able to both dissipate the large heat loads and meet the diminishing size requirements. Microchannel heat exchangers have become an integral part of such advanced cooling systems as they provide an exceedingly large surface area over which heat transfer can occur while maintaining a diminutive size. Current microchannel devices primarily use single-phase flow to dissipate the heat. As heat loads increase, so too must flow rates. Due to associated issues with extremely large pressure drops and high pumping power requirements, the practical capacity of single-phase microchannel coolers has largely been met. One particularly promising avenue forward is to utilize flow boiling with similar microchannel heat exchanger designs. The very high latent heat of vaporization associated with phase change for many fluids allows for a large amount of heat to be dissipated in flow boiling using a relatively low flow rate as compared to single-phase systems, drastically reducing the issues related to pressure drop. Additionally, two-phase heat transfer is associated with much higher heat transfer coefficients, allowing for smaller heat transfer surface areas (and thus smaller overall devices) and lower driving temperature differences for the same heat removal rates. Microchannel flow boiling studies to date have assumed 1D heat conduction through the heat exchanger material and have developed correlations to predict average heat transfer coefficients. Unfortunately, with the high heat fluxes expected in the near future, and with heat loads being applied at small, localized hotspots, the 1D assumption is no longer valid. Conjugate heat transfer must be considered, and local heat transfer coefficient correlations are necessary for the design of future thermal management systems. This thesis describes a first of its kind computational model that uses finite element analysis to analyze the conjugate heat transfer problem, complete with local heat transfer coefficients. This work serves as both proof of concept and an evaluation of the predictive capabilities of five published heat transfer correlations when applied locally to a high heat flux microchannel heat exchanger that has been previously tested. Modeling results show highly variable local heat flux profiles along the microchannel walls, confirming the need to consider conjugate heat transfer. Significant heat spreading resulted in peak local heat fluxes of roughly 0.5× that of the uniformly applied heat flux with 31.4% - 64.1% of total applied heat dissipated outside the region projected directly above the heater. As determined via local temperature comparisons, the correlation from Agostini and Bontemps provides the best overall agreement with average root mean square temperature differences of 2.6°C, though trends suggest that this difference may increase as heat flux increase further than those values tested here.
Keywords: flow boiling; conjugate heat transfer; microchannel